Distributed dynamic modelling of suspended sediment mobilization and transport from small agricultural catchments - Sandström, Sara; Markensten, Hampus; Futter, Martyn N.; Kyllmar, Katarina; O’Connell, David W.; Bishop, Kevin; Djodjic, Faruk (Frontiers in Environmental Science, 2023)
Erosion, soil loss and consequent nutrient fluxes impair water quality and can degrade arable soils. Erosion rates in Sweden are generally low but episodic losses of suspended solids (SS) can affect water quality. Identifying critical source areas (CSAs) and "hot moments" is essential to reduce erosive losses from arable land. Here we use a distributed, dynamic high-resolution erosion model that simulates the sum of all transported material, i.e. erosion within the soil profile, on the soil surface and transport through drainage systems. We simulate monthly SS transport in six small agricultural catchments with varying soil texture over eight years. Kling-Gupta Efficiency (KGE) was used as model performance statistics, and calibration (KGE=0.45-0.78) and validation (KGE=0.64-0.83) showed acceptable model performance for all catchments, with mean annual SS losses between 2.1-31.5 t km-2yr-1. Equifinality could be minimised by using more precise initial parameter values. We suggest that the model can be applied to comparable unmonitored catchments to identify erosion-sensitive periods and CSAs.